Identification of Aeromonas Salmonicida and Edwardsiella Ictalury in Live Fish that Will Be Trafficked from Yogyakarta Special Region - Anggi Rusita Rahmawati; Mohammad Faizal Ulkhaq; Dewi Susanti; Hapsari Kenconojati; Arif Habib Fasya (Universitas Airlangga, 2021)
The freshwater aquaculture fishery sector in Indonesia has the potential to be developed through extensification and intensification. The problem in aquaculture is diseases that infects cultivated organisms, one of which is caused by bacterial infection. Bacterial infection can cause huge losses to cultivation activities, including death which results in economic losses. The purpose of this study is to identify the A. salmonicida and E. ictalury in live fish that will be exported from DI Yogyakarta. The method of examining bacteria used is conventional which consists of isolation, purification, presumptive test, biochemical test, and identification. The results showed that all live fish samples (koi, gouramy, goldfish, catfish, and eel) were not infected with A. salmonicida and E. ictalury. This shows that all live fish are in a healthy condition and suitable to be exported of DI Yogyakarta.